2003
DOI: 10.1124/mi.3.8.441
|View full text |Cite
|
Sign up to set email alerts
|

A Neurogenic Theory of Depression Gains Momentum

Abstract: The rate of adult neurogenesis fluctuates in response to several environmental factors. Chronic stress, which can lead to neuronal apoptosis and dendritic atrophy, certainly affects the overall rate of neurogenesis in the adult brain. Depression, which arises from several causes, including chronically stressful situations, is known to correlate with altered hippocampal morphology. But is the link between depression and neuronal regeneration merely coincidental? Recent studies indicate that ingestion of antidep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Moreover, chronic alcohol reduces hippocampal neurogenesis (Nixon and Crews, 2002) but the behavioral effects of antidepressant medications may require hippocampal neurogenesis (Santarelli et al, 2003). These and other findings have led to emerging theories that implicate a CREB-BDNF-neurogenesis pathway in both the etiology of depression and antidepressant efficacy Malberg et al, 2000;Thomas and Peterson, 2003). Overall, CREB and BDNF activity in the dentate gyrus appear to be important mediators of antidepressant efficacy and raise the hypothesis that decreases in p-CREB, such as those that occur after chronic alcohol, have the potential to induce behavioral despair and reductions in neurogenesis as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, chronic alcohol reduces hippocampal neurogenesis (Nixon and Crews, 2002) but the behavioral effects of antidepressant medications may require hippocampal neurogenesis (Santarelli et al, 2003). These and other findings have led to emerging theories that implicate a CREB-BDNF-neurogenesis pathway in both the etiology of depression and antidepressant efficacy Malberg et al, 2000;Thomas and Peterson, 2003). Overall, CREB and BDNF activity in the dentate gyrus appear to be important mediators of antidepressant efficacy and raise the hypothesis that decreases in p-CREB, such as those that occur after chronic alcohol, have the potential to induce behavioral despair and reductions in neurogenesis as seen in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this view is that stress diminishes neurogenesis, and clinical depression is often associated with stress (Jacobs et al, 2000a,b). It has even been concluded that neurogenesis is a "requirement" for certain antidepressant behavioral effects (Santarelli et al, 2003), but it is still unknown whether diminished neurogenesis could be a cause, a consequence, or a correlate of depression (Gage, 2000;Thomas and Peterson, 2003). It is an important finding that an acute episode of psychosocial stress did not alter proliferation or immediate survival, as evidenced by IdU/CldU administration in experiment 1, but it did alter short-and long-term survival as shown in experiments 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports indicate an association between depression and hippocampal atrophy which may partially result from excessive programmed cell death (Lee et al, 2002 ;Thomas and Peterson, 2003). Both TNF-a and IL-1b were found to be potent proapoptotic factors of the nervous cells (Downen et al, 1999 ;Ma et al, 2002Ma et al, -2003.…”
Section: Discussionmentioning
confidence: 96%